La representación del mundo en los informativos de televisión - Díaz Arias, Rafael (Estudios sobre el Mensaje Periodístico, 2008)
This paper discusses the way in which the tv newscasts conform the image of the world, using a portion of an empirical investigation on the TVE news. It seeks to answer the question of whether TV newscasts promoting the culture of fear. We analyze the scientific literature on factors that becomes an event in a news in international information: the critical school defends that the media deforms the image of the peripheral countries and stresses the factor of national interests to select events; the professional school explores empirically the “news values” and concluded that the newness and proximity play a particularly important role. The findings of the scientific literature are confronted with the empirical study of the television news in TVE. The conclusion is that the represented world is threatening, institutional and interdependent, with an approach that seeks to smooth the more negative aspects. The relationship with Spain is one of the decisive factors for an event outside our borders becomes news.
Keywords: Foreign news; Image of the world; News values